Moving forward: power house marketing Sdn. Bhd - Saleh, Rosli; Loh, Hong Wuh (Universiti Putra Malaysia Press, 2013)
Power House Marketing Sdn. Bhd. (319135-D) is an apparel manufacturing company, owned by the Liew brothers, who started their operation in 1981 and possess brands such as Blue Toms Jeans Inc ™, Toms Girl Authentic Wear™, O’REEF™, Müller™, and PH Concept. Their product mainly focuses on adult casual apparels for both men and women, such as shirts, pants and shorts. For the past five years, the level of sales has remained almost stagnant, and the company is facing a reduction in profit margin as a result of fluctuation in the USD to MYR currency exchange rate and an increase in the price of cotton and fuel. The company would like to re-strategize their product differentiation strategy and improve customer satisfaction by providing quality products. The company currently faces internal issues such as a lack of manpower with management skills and a sense of responsibility. Apart from that, the company has a very limited advertising effort in all parts of the media, and this may have created a threat, as or competitors may vie for additional market share. Furthermore, given the growth of the middle income population, the company sorely needs to develop strategies to capitalize on this growth.